The Survey of association between health literacy and BMI among adolescents - Farideh saedi; Rahman Panahi (Mashhad University of Medical Sciences, 2017)
Background and objective: Health literacy includes the capacity to understand and act on messages which is the center of critical judgments and decisions not only within the health care environments but also about health issues. The relationship between health literacy of adolescents and body mass index has been less studied. Therefore, the present study examines the relationship between health literacy and BMI among adolescents. Methods: This cross-sectional and descriptive-analytical study conducted on 400 male and female students studying in the second period of high schools, who were selected by multistage random sampling. Data were collected using questionnaire containing demographic characteristics, health literacy (questionnaire of HELMA) and BMI-related questions. Data were analyzed using SPSS version 20 and appropriate tests. Results: 37.5% (n=150) had inadequate health literacy, 37% (n = 148) not so adequate health literacy, 22.5% (n = 90) adequate health literacy and 3% (n = 12) had excellent health literacy. The mean and standard deviation of mean body mass index of subjects was calculated as 23.63 4.89, respectively. There was no significant and Strong correlation between health literacy level and body mass index. Conclusion: Due to lack of relationship between health literacy and BMI it seems that various other variables besides health literacy influence body mass index. Paper Type: Research Article.